Tree Composition and Distribution of the Gunung Bubu Virgin Jungle Reserves, Perak Phytogeographical Subprovince - Zahid Mat Said, Mohmadisa Hashim, Nasir Nayan, Yazid Saleh, Hanifah Mahat (International Journal of Advanced Science and Technology, 2020)
This study aim to identify tree composition and distribution in the Gunung Bubu Virgin Jungle Reserves (VJR), Perak, Malaysia. The methodology used plot study technique where 20 subplots of 20 m x 25 m were established randomly in the Compartment 6 and 7 of Gunung Bubu VJR. The total area enumerated was 1-ha. Tree with diameter at breast height (DBH) of 5 cm and above were censured. The trees vouchers were taken and identified by referring to specimens collections available in the herbarium of Universiti Kebangsaan Malaysia (UNIKEB) and also by using the keys and description of Whitmore (1972; 1973). The family, genus and species distribution data were laid out and displayed. In total 779 individual trees were identified. This number was made up by 45 families, 122 genera and 215 species. The highest number of trees for the families rank is Euphorbiaceae (88 stands), followed by Moraceae (80 stands), Dipterocarpaceae (58 stands), Ebenaceae (40 stands) and Burseraceae (38 stands). The families mentioned described the Gunung Bubu VJR tree family composition. The highest number of trees for genus rank is Shorea (48 stands), Streblus (43 stands), Diospyros (40 stands), Artocarpus (35 stands) and Anisophyllea (25 stands). Shorea, with the highest tree stands illustrated that Gunung Bubu VJR is typically the lowland dipterocarp forest formation. Shorea and Streblus have the highest frequency distribution of the genus rank with a value of 17. The highest number of trees in the species rank is Shorea parvifolia (39 stands), Streblus elongatus (25 stands), Ixonanthes icosandra (17 stands), Diospyros sumatrana (17 stands) and Pellacalyx axillaris (16 stands). Shorea parvifolia (Dipterocarpaceae) with the highest frequency and tree stand in species rank indicated that the Gunung Bubu VJR is well represented with typical lowland dipterocarps forest of Malaysia. The tree composition of Gunung Bubu VJR contributed to the richness and uniqueness of Perak Phytogeographical subprovince.